2016
DOI: 10.1146/annurev-pharmtox-010715-103255
|View full text |Cite
|
Sign up to set email alerts
|

My Winding Road: From Microbiology to Toxicology and Environmental Health

Abstract: I would certainly never have predicted that I would become the director of the National Institute of Environmental Health Sciences (NIEHS) and the National Toxicology Program (NTP) when I was a Jewish girl growing up in Teaneck, New Jersey. My family stressed the importance of education. Yet for a girl there were many not-so-subtle suggestions that the appropriate careers were in teaching or nursing, and the most important thing was to be a wife and mother. Well, I can't disagree with the latter, although I wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Development of high-throughput screening (HTS) and in vitro profiling assays in recent years has generated advances towards providing the experimental throughput, target specificity, and computational capabilities necessary to thoroughly investigate vascular developmental toxicity. For example, the US EPA's ToxCast program and the Tox21 consortium generate in vitro HTS data on 1000's of chemicals against 100's of molecular targets and biological pathways [12] [13]. These HTS data facilitate chemical hazard identification to support chemical prioritization efforts for further evaluation under existing regulatory requirements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Development of high-throughput screening (HTS) and in vitro profiling assays in recent years has generated advances towards providing the experimental throughput, target specificity, and computational capabilities necessary to thoroughly investigate vascular developmental toxicity. For example, the US EPA's ToxCast program and the Tox21 consortium generate in vitro HTS data on 1000's of chemicals against 100's of molecular targets and biological pathways [12] [13]. These HTS data facilitate chemical hazard identification to support chemical prioritization efforts for further evaluation under existing regulatory requirements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent exhaustive and comprehensive studies of drug molecules and their diverse interactions demonstrated that target diversity is common for approved drugs, and some of the unanticipated pathways detected through modeling and broad screening could affect drug action [114,115]. The discovery of new targets for existing GPCR drugs could lead to drug repurposing, a current area of concentration for NIH [116]. The binding of a series of sterically constrained nucleosides at various GPCRs, as determined empirically, was analyzed showing consistent structural association [35], which can now be used to modify the ligands to augment or diminish polypharmacology.…”
Section: New Pharmacological Dimensionsmentioning
confidence: 99%
“…I’ve been asked to share some brief thoughts about my career of over 40 years. I have recently written an invited autobiography by Annual Reviews of Pharmacology and Toxicology, “My Winding Road: From Microbiology to Toxicology and Environmental Health.” 1 It’s a pretty detailed tale of how my life, and career, has developed. It also addressed many of the questions that I’ve been asked to address, starting with how I got started in science, the challenges I’ve faced, and to what I really think is most important to be successful in science.…”
mentioning
confidence: 99%